Pertarungan Kekuasaan dan Dinamika Sosial: Memahami Perspektif Baru - Ibnu, Syahrir; Nasim, Abu Sahman; Zainuddin Arifin; Rahmatullah; Afrilia, Ufa Anita (JOM, 2024)
Power struggles and social dynamics are important topics in the study of social science and politics because they illustrate how power influences the structure and functioning of society. In the era of globalization, information technology and mass migration, these dynamics are increasingly complex and have an impact on social and political changes throughout the world. In response to this phenomenon, there is a need to understand how power is seized, exercised and maintained amidst rapid social change. The aim of this research is to analyze the role of technology, globalization, and societal responses in influencing power structures and social dynamics. This research uses a descriptive qualitative approach with data originating from relevant previous studies. Data is collected and processed to identify patterns that show the interaction between power and social change. The conclusions of this research show that technology has significantly changed the way power is gained and exercised, giving minority groups more voice but also creating new challenges in the control of information. Globalization has influenced domestic policies and widened economic disparities, while international organizations play an increasingly important role in global politics. Society shows a variety of responses to changes in power, from adaptation to resistance, with the media and social movements playing a key role in this process. Understanding these dynamics is important for navigating social and political change in an ever-changing global context.